The Western Balkans and the EU in Multilateral Organisations: Foreign Policy Coordination and Declaratory Alignment in the OSCE - Marciacq, Florent (Journal of Regional Security, 2018)
This paper sheds light on the Europeanisation of Western Balkan states’ multilateral diplomacy in the Organisation for Security and Cooperation in Europe (OSCE). More specifically, it enquires into the politics of declaratory alignment of six Western Balkan states. It analyses the frequency at which those states have aligned themselves with the statements of the European Union (EU) between 2004 and 2011, and researches qualitatively the motives of their alignment. The paper finds that the declaratory behaviour of most Western Balkan states in the OSCE has become distinctively convergent with EU positions. Although conditionality certainly fosters alignment, the paper shows that socialisation is a more powerful mechanism of diffusion for most Western Balkan states; that emulation should not be neglected amongst small-sized countries; and that coercion and, interestingly, persuasion do not play a significant role.